PENGARUH DUKUNGAN ORANG TUA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 8 KOTA JAMBI - Redi Indra Yudha, Kasiono, (SJEE (Scientific Journals of Economic Education), 2017)
This study aims to find out the description of parental support, motivation to learn, student learning outcomes, and the influence of parent support and motivation to learn the results of students of class X on economic subjects in SMA Negeri 8 Kota Jambi. The result of the research explain that the variable of parent support and learning motivation are in good category, while the learning result variable is still many students who have not complete in following the learning process on economic subjects in SMA Negeri 8 Kota Jambi. Meanwhile, it is known parent support and motivation to learn either partially or simultaneously have positive value and have a significant effect on the result of student learning of class X on economic subjects in SMA Negeri 8 Kota Jambi. That is, in achieving optimal learning outcomes, students must not only have the motivation to learn without the support of their respective parents.Kata Kunci : Support Parents, Learning Motivation, Learning Outcomes